Psychological risk, security risk and perceived risk of the cryptocurrency usage - Mirza, Agus Muhammad; Fernando, Yudi; Mergeresa, Fineke; Wahyuni-Td, Ika Sari; Ikhsan, Ridho Bramulya; Fernando, Erick (Institute of Electrical and Electronics Engineers Inc., 2023)
Today's technology is increasingly advanced and developing, changing payment and investment methods. The emergence of crypto currencies represents the most recent innovation. Cryptocurrencies have attracted the attention of information technology professionals, economists, investors, banks and governments. However, aside from the advantages, there is also the expectation of cryptocurrencies of potential risks in using currency. This study aims to identify the factors influencing the decision to use cryptocurrency. The factors discussed are perceived risk, psychological risk and security risk. This study used a purposive sampling technique. The data were analysed using PLS-SEM with a final sample of 181 respondents. The results show that psychological, security and perceived risks significantly affect cryptocurrency usage. A relatively new technology makes it easier for individuals to make decisions about using cryptocurrencies. However, lack of information often causes individuals to face uncertainty and various levels of risk. However, individual decisions in using technology are not only influenced by risks but also benefit factors.